2023
DOI: 10.1007/s40121-023-00800-6
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Risk Factors of Clostridioides difficile Infections in Germany: A Health Claims Data Analysis

Abstract: Introduction Clostridioides difficile infection (CDI) is increasingly recognized as a public health threat at the community level in addition to being one of the most common causes of healthcare-associated infections. In Germany, the epidemiology of CDI is primarily informed by national hospital-based CDI surveillance. We used health claims data from Germany to obtain valuable insights on population-level disease burden and risk factors for CDI. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…However, the use of antibiotics is likely underestimated since hospital-dispensed treatments are not recorded in the BKK database. Like other studies, there was a higher proportion of female patients in our study [ 5 , 36 38 ]. So far, no association has however been found between gender and susceptibility to CDI.…”
Section: Discussionsupporting
confidence: 82%
“…However, the use of antibiotics is likely underestimated since hospital-dispensed treatments are not recorded in the BKK database. Like other studies, there was a higher proportion of female patients in our study [ 5 , 36 38 ]. So far, no association has however been found between gender and susceptibility to CDI.…”
Section: Discussionsupporting
confidence: 82%
“…Comorbidities are common among patients with CDID and are generally reported as not only a risk factor for this disease, but also for its complications and even reduction in survival [59][60][61][62]. Thus, we evaluated the influence of comorbidities in patients with concordant treatment, and our study revealed severe comorbidities to be significantly related to reduced 30-day survival and increased 30-day all-cause mortality, as well as to be a predictor for 30-day all-cause mortality.…”
Section: Discussionmentioning
confidence: 87%